PENGARUH GAYA KEPEMIMPINAN DOSEN MATEMATIKA DAN BUDAYA AKADEMIK TERHADAP KETERLIBATAN BELAJAR MAHASISWA DENGAN SELF-EFFICACY - Kurniawan, Choirul; Abidin, Munirul (Universitas Insan Budi Utomo, 2026)
This study aims to analyze the influence of Mathematics Education lecturers' leadership style and academic culture on student learning engagement with self-efficacy as a mediating variable. Student learning engagement is an important aspect in the learning process in higher education, which is influenced by both internal and external factors. Lecturers' leadership style and academic culture are seen as external factors that play a role in shaping student self-efficacy as an internal factor. This study uses a quantitative approach with a survey method that collects information from a specific sample or population through systematic questions to determine the attitudes, opinions, behaviors, or characteristics of respondents. The research subjects were students of the Mathematics Education Study Program who were selected using a sampling technique, a method used to select a portion of the population (sample) to represent the entire population in a study. This technique is important in research in fields such as Statistics, Social Sciences, and Research Methodology. Data collection was carried out through questionnaires that have been tested for validity and reliability. Analysis using IBM SPSS Statistics is the process of processing and analyzing research data (usually quantitative data) with the help of SPSS statistical software to test the direct and indirect effects between variables. The results of the study indicate that lecturers' leadership style and academic culture have a significant effect on student learning engagement. Furthermore, self-efficacy was shown to act as a mediating variable, strengthening the influence of lecturer leadership style and academic culture on student learning engagement. These findings indicate that increasing student learning engagement can be optimized through developing effective lecturer leadership styles, a conducive academic culture, and strengthening student self-efficacy.